Assessing the Use of Performance Based Assessments and Portfolios-Principles and Processes of Outcome Based Curriculum in Botswana - Modise, Moya (Advances in Social Sciences Research Journal, 2025)
Background is that Human Resource Development Council Review (2024) highlights a skills mismatch in Botswana’s labor market. The review points out that graduates often possess more theoretical knowledge than practical skills, underscoring the need to profile skills and competency gaps (https://www.resaerchgate.net/profile/sue-askew/publication/27469567-potfolios for learning assessment and professional development in highereducation). Rationale for using Performance Based Assessments and Portfolios-Principles and Processes of Outcome Based Curriculum is that they help educators apply principles, processes and procedures of developing, assessing and moderating Outcome Based Curriculum / syllabus / content to equip learners to execute enabling outcomes-performance criteria outcomes-learning outcomes-culminating outcomes (apply-analyze-synthesize-create-evaluate-solve) real life and hypothetical situations. This study evaluates the application of Principles and Processes of Outcome Based Curriculum-Performance Based Assessments and Portfolios in Botswana. It investigates whether the Principles and Processes of Outcome Based Curriculum is reflected during the implementation of Botswana curriculum, specifically Foundations of Education curriculum at Serowe College of Education. Qualitative research approach; purposive sampling was used to select respondents who could best provide answers to the research objectives in this study. Qualitative analysis was used to synchronize and analyze data from the following various sources using triangulation under each research objective or theme: Principles of assessment and moderation in Outcome Based Curriculum; qualitative interviews from Course: FOE 111 Educational Psychology (Theories of Child Development and Human Learning) & Course: FOE 122 Early Childhood Education; ethnographic design participant in-depth immersion personal observations and experiences of the researcher; Question and answer during FOE meeting; End of Semester Moderation and Quality Assurance Report; relevant theories and philosophies. Findings: Principles and Processes of Outcome Based Curriculum are applied in Performance Based Assessments and Portfolios in Botswana. Model or approach to assessing Performance Based Assessments and Portfolios lived in Botswana-Serowe College of Education Curriculum is a hybrid of [Portfolios:-execute enabling outcomes (small skills)-performance criteria outcomes-learning outcomes-culminating outcomes (apply-analyze-synthesize-create-evaluate-solve) in real life and hypothetical situations)] + [End of Semester written examinations conditioning learners to apply-analyze-synthesize-create-evaluate-solve in real life and hypothetical situations under a specific allocated time to enhance learners ability to function efficiently and effectively under a given time frame]. Quality assurance standards that Performance Based Assessments and Portfolios should meet are applied in Botswana. The two models or approaches to assessing an Outcome Based Curriculum (OBE) in Botswana are in line with Principles and Processes of Outcome Based Curriculum and therefore should be retained or maintained. Recommendations: To implement OBC effectively, consider the following steps: Define Clear Learning Outcomes: Ensure that each course has specific, measurable outcomes that students are expected to achieve. Design Assessment Methods: Choose assessment methods that align with these outcomes. This could include portfolios, projects, presentations, exams, and other activitieshttp://en.wikipedia.org/wiki/outcome-based-education. Provide Continuous Feedback: Use formative assessments to give students regular feedback on their progress. Summative Evaluation: Decide whether to use portfolios, exams, or a combination of both for final assessment. Grading System: Determine whether to use a pass/fail system or a more detailed grading scale. Significance of the study is that results obtained in this work will help ensure that a hybrid of [Portfolios:-execute enabling outcomes-performance criteria outcomes-learning outcomes-culminating outcomes (apply-analyze-synthesize-create-evaluate-solve) in real life and hypothetical situations] + [End of Semester written or practical examinations where learners apply-analyze-synthesize-create-evaluate-solve in real life and hypothetical situations under a specific allocated time to enhance learners’ ability to execute skills efficiently and effectively in given specific times].